Tanggung Jawab Pejabat Pembuat Akta Tanah (PPAT) Dalam Pendaftaran Peralihan Hak Milik Atas Tanah - Dewi Rasda; Muhammad Sabir Rahman; Bakhtiar Tijjang (Jurnal Litigasi Amsir, 2021)
The general office of the Land Deed Making Official who is authorized to make deeds regarding land, of course, must have special abilities and skills in the land sector so that the deed he makes does not cause problems in the future. land-based on Government Regulation Number 24 of 1997 concerning land registration. This research uses normative and empirical research with a statutory approach. The data sources use primary legal materials and secondary legal materials. The results of this study indicate that the responsibility of the Land Akat Maker Official in the Implementation of Land Registration at the ATR/BPN Office of Parepare City is that the Land Akat Maker Official is responsible for providing legal protection to the parties that arise because of an unlawful act he did in carrying out his duties. The Land Deed Making Officer as the delegate is administratively responsible if there is a mal-administration in the making of an authentic deed, the Land Akat Making Officer is responsible for the legality of legal actions according to data from the statements of the appearers and guarantees the authenticity of the deed and is responsible that his actions are following the procedures.